Analysis and modelling of cholesterol and high-density lipoprotein cholesterol changes across the range of C-reactive protein levels in clinical practice as an aid to better understanding of inflammation–lipid interactions. Issue 8 (28th May 2013) - Johnsson, Hanna; Panarelli, Maurizio; Cameron, Allan; Sattar, Naveed
Abstract : Objectives: Raised total cholesterol (TC) and reduced high-density lipoprotein (HDL) cholesterol levels are established cardiovascular disease (CVD) risk factors. However, in autoimmune conditions the lipid–CVD association appears paradoxical, with inflammation as a potential confounding factor. We therefore sought to model the relationship between systemic inflammatory illness and lipid levels using C-reactive protein (CRP) as the prototypical marker of inflammation. Our hypothesis was that there would be an inverse association between raised CRP levels and both TC and HDL-cholesterol levels. Methods: Results from samples analysed simultaneously for CRP and lipids in a 6-month period were collected retrospectively from a large city hospital laboratory database that collates results from both primary and secondary care. The relationships between CRP and lipids were determined using graphical techniques and empirical, non-parametric, best fit models. Results: A total of 11 437 blood samples was included. We identified a significant (p<0.001) biphasic relationship between TC and CRP: TC increased within the healthy CRP range of less than 5 mg/l, but decreased with CRP levels above 10 mg/l. The two effects approximately cancelled each other out in the intermediate CRP range of 5–10 mg/l. There was an inverse relationship between HDL-cholesterol and CRP. Conclusions: Lipid levels change significantly during inflammatory illness in a population with both acute and chronic conditions. These results provide a strong epidemiological basis for the better understanding of lipid changes in inflammatory conditions and with anti-inflammatory therapies.